IMPLEMENTASI METODE CIBEST (CENTER OF ISLAMIC BUSINESS AND ECONOMIC STUDIES) DALAM MENGUKUR PERAN ZAKAT PRODUKTIF TERHADAP PEMBERDAYAAN MUSTAHIQ DI LEMBAGA YAYASAN DANA SOSIAL AL-FALAH (YDSF) SURABAYA1 - Muhammad Afthon Ashar; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Productive zakat is the management of zakat funds by providing assistance in the form of business activity funds to mustahiq. The purpose of productive zakat funds to the community is to improve the economic welfare of mustahiq. CIBEST (Center of Islamic Business and Economic Studies) is a method of measuring mustahiq poverty that is based not only on material aspects, but spiritual mustahiq before and after obtaining assistance from zakat funds. This study aims to determine the condition of mustahiq poverty before and after receiving assistance from zakat funds Al-Falah Social Fund Foundation, Surabaya City. The approach used in research is a quantitative approach with case studies. In the technique of collecting data using interview techniques directly to Mustahiq based on questionnaires. The result of this study is that there is a change in the condition of the Mustahiq Quadrant I family (Prosperous) before getting zakat assistance, namely 3 heads of families to 5 heads of families. Quadrant II (Material Poverty) before getting zakat assistance, namely 1 family head, 0 family heads. Quadrant III (Spiritual Poverty Index) before getting help from one family head, 3 family heads. Quadrant IV (Absolute Poverty) before getting zakat assistance, namely 4 heads of families, becomes 0 family heads.Keywords: Productive Zakat, CIBEST, MustahiqREFFERENCESAnshori Muslich dan Sri Iswati. 2009. Metode Penelitian Kuaantitatif. Surabaya: Airlangga University Press (AUP)Asnaini. 2008. Zakat Produktif Dalam Perspektif Hukum Islam. Bengkulu: Pustaka Pelajar. Azam, M., Iqbal, N., & Tayyab, M. (2014). Zakat and Economic Development: Micro and Macro Level Evidence from Pakistan. Bulletin of Business and Economics, 3(2), 85-95.Badan Pusat Statistik (BPS). 2016. Profil Kemiskinan di Indonesia Maret 2018. dalam Berita Resmi Statistik, edisi No.57/07/Th.XXI, 16 Juli 2018. Badan Pusat Statistik. Jakarta.Badan Pusat Statistik (BPS). 2016. Profil Kemiskinan Kota Surabaya 2018. dalam Berita Resmi Statistik, edisi No.01/01/3578/ Th.II, 04 Januari 2018. Badan Pusat Statistik. Jakarta.Beik IS, Arsyianti LD. 2015. Ekonomi Pembangunan Syariah. Bogor (ID) edisi revisi : IPB Press.Fakhruddin. 2008. Fikih dan Manajemen Zakat di Indonesia. Malang: UIN Malang Press Firdausi, Hilya. 2015. “Peran Dana Zakat Produktif Dalam Mengembangkan Usaha Mustahik (Studi Kasus Pada Lembaga Amil Zakat Masjid Al Akbar Surabaya). Skripsi. Surabaya: Fakultas Ekonomi dan Bisnis, Universitas Airlangga.Imaduddin Abi Al-Fida’i Ismail Ibn Katsir Al-Qurasyiyyi. 1995. Tafsir Al-Qur’an Al-Azhim jilid 2. Riyadh: Daar ‘Alimi Al-Kutub.Hamzah Hasan Khaeriyah. 2008. Ekonomi Islam, Kerangka Fikir dan Istrumen Ekonomi Zakat Serta Wasiat. Jakarta: Lekas.Hikmat Kurnia, dan A Hidayat. 2008. Panduan Pintar Zakat. Jakarta: Qultum Media.Nindityo, Herwindo Ghora.2014.“Zakat Produktif Untuk Meningkatkan Kinerja Produksi, Motivasi, dan Religuitas Mustahik (Studi Kasus Pada BAZ Jatim)". Skripsi. Surabaya: Fakultas Ekonomi dan Bisnis, Universitas Airlangga.Sugiyono. 2009. Metode Penelitian Kuantitatif, Kualitatif Dan R&D. Bandung: Alfabeta.Sugiyono. 2017. Metode Penelitian Kuantitatif, Kualitatif dn R&D. Bandung: AlfabetaTarigan, Josep R., M. Suparmoko. 2000. Metode Pengumpulan Data : Untuk Ilmu Sosial dan Ekonomi. Jilid 1. Yogyakarta : BPFE.Yusuf Qardhawi. 2007. Hukum Zakat.Jakarta : Lentera Antar Nusa http://www.bps.go.id/ , dikases pada tanggal 23 Maret 2017http://www.surabayakota.bps.go.id/, diakses pada tanggal2 Juni 2017http://www.ydsf.org, diakses pada tanggal 2 Juni 2017